Mechanism of Input Tax Calculation on Medical Service at PT BEC - Ni Luh Linda Muliasih; I M M Arsana; Istiarto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
PT BEC is a taxable entrepreneur engaged in eye health. Every month PT BEC credits all Input Taxes with Output Tax. This cannot be made because there are elements of Input Tax that cannot be credited, so it is necessary to calculate Input Tax by referring to the Regulation of the Minister of Finance Number 135/PMK.11/2014 to know for sure the amount of Input Tax that can be credited. The main purpose of this research is to find out the calculation of the creditable Input Tax which is more efficient to be carried out by PT BEC in terms of the amount of expenditure used by PT BEC to pay the VAT owed, by calculating the Creditable Input Tax every month and only once at the end of the year. This research is a qualitative research with a case study approach. The analysis technique in this research is descriptive qualitative analysis using secondary data and data collection is done through unstructured interviews, documentation, and observation. The results showed that the calculation of the creditable Input Tax which was carried out only once at the end of the year was more effective for PT BEC because there was a savings of Rp1.458.490.